Spatial Physiological Heterogeneity in Pseudomonas aeruginosa Biofilm Is Determined by Oxygen Availability - Xu, Karen D. (American Society for Microbiology, 1998)
The role of oxygen availability in determining the local physiological activity of Pseudomonas aeruginosa growing in biofilms was investigated. Biofilms grown in an ambient-air environment expressed approximately 1/15th the alkaline phosphatase specific activity of planktonic bacteria subjected to the same phosphate limitation treatment. Biofilms grown in a gaseous environment of pure oxygen exhibited 1.9 times the amount of alkaline phosphatase specific activity of air-grown biofilms, whereas biofilms grown in an environment in which the air was replaced with pure nitrogen prior to the inducing treatment did not develop alkaline phosphatase activity. Frozen cross sections of biofilms stained for alkaline phosphatase activity with a fluorogenic stain demonstrated that alkaline phosphatase activity was concentrated in distinct bands adjacent to the gaseous interfaces. These bands were approximately 30 μm thick with biofilms grown in air, 2 μm thick with biofilms grown in pure nitrogen, and 46 μm thick with biofilms grown in pure oxygen. Overall biofilm thickness ranged from approximately 117 to approximately 151 μm. Measurements with an oxygen microelectrode indicated that oxygen was depleted locally within the biofilm and that the oxygen-replete zone was of a dimension similar to that of the biologically active zone, as indicated by alkaline phosphatase induction. These experiments revealed marked spatial physiological heterogeneity within P. aeruginosa biofilms in which active protein synthesis was restricted by oxygen availability to the upper 30 μm of the biofilm. Such physiological heterogeneity has implications for microbial ecology and for understanding the reduced susceptibilities of biofilms to antimicrobial agents.